The M33 G Protein-Coupled Receptor Encoded by Murine Cytomegalovirus Is Dispensable for Hematogenous Dissemination but Is Required for Growth within the Salivary Gland - Bittencourt, Fabiola M. (American Society for Microbiology, 2014)
Human cytomegalovirus (HCMV) is a pathogen found worldwide and is a serious threat to immunocompromised individuals and developing fetuses. Due to the species specificity of cytomegaloviruses, murine cytomegalovirus (MCMV) has been used as a model for in vivo studies of HCMV pathogenesis. The MCMV genome, like the genomes of other beta- and gammaherpesviruses, encodes G protein-coupled receptors (GPCRs) that modulate host signaling pathways presumably to facilitate viral replication and dissemination. Among these viral receptors, the M33 GPCR carried by MCMV is an activator of CREB, NF-κB, and phospholipase C-β signaling pathways and has been implicated in aspects of pathogenesis in vivo, including persistence in the salivary glands of BALB/c mice. In this study, we used immunocompetent nonobese diabetic (NOD) and immunocompromised NOD-scid-gamma (NSG) mice to further investigate the salivary gland defect exhibited by M33 deficiency. Interestingly, we demonstrate that virus with an M33 deletion (ΔM33) can replicate in the salivary gland of immunocompromised animals, albeit with a 400-fold growth defect compared with the growth of wild-type virus. Moreover, we determined that M33 does not have a role in cell-associated hematogenous dissemination but is required for viral amplification once the virus reaches the salivary gland. We conclude that the reduced replicative capacity of the ΔM33 virus is due to a specific defect occurring within the localized environment of the salivary gland. Importantly, since the salivary gland represents a site essential for persistence and horizontal transmission, an understanding of the mechanisms of viral replication within this site could lead to the generation of novel therapeutics useful for the prevention of HCMV spread. IMPORTANCE Human cytomegalovirus infects the majority of the American people and can reside silently in infected individuals for the duration of their lives. Under a number of circumstances, the virus can reactivate, leading to a variety of diseases in both adults and developing babies, and therefore, identifying the function of viral proteins is essential to understand how the virus spreads and causes disease. We aim to utilize animal models to study the function of an important class of viral proteins termed G protein-coupled receptors with the ultimate goal of developing inhibitors to these proteins that could one day be used to prevent viral spread.